2021
DOI: 10.1371/journal.pntd.0009716
|View full text |Cite
|
Sign up to set email alerts
|

Innovative tracking, active search and follow-up strategies for new leprosy cases in the female prison population

Abstract: Background Regarding the leprosy transmission through the upper airways, overcrowded locations such as prisons can become a risk to get sick. Like the leprosy hidden endemic demonstrated in male prison population, being interesting to assess the leprosy scene also among confined women. Methods A prospective descriptive study conducted at Female Penitentiary, Brazil. Leprosy Suspicion Questionnaire (LSQ) were applied to the participants, and submitted to specialized dermatoneurological exam, peripheral nerve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
0
7
0
4
Order By: Relevance
“…Prevalence of HIV varied from 1% (Viitanen et al , 2011) to 18.8% (Smith et al , 1991). Silva and colleagues (2021) identified 14 leprosy cases in their sample from Brazil, implying a detection rate of 3.5%.…”
Section: Resultsmentioning
confidence: 99%
“…Prevalence of HIV varied from 1% (Viitanen et al , 2011) to 18.8% (Smith et al , 1991). Silva and colleagues (2021) identified 14 leprosy cases in their sample from Brazil, implying a detection rate of 3.5%.…”
Section: Resultsmentioning
confidence: 99%
“…A realização de campanha de busca ativa em unidade prisional feminina brasileira, em que foi utilizado o questionário de suspeição de hanseníase, permitiu realizar o diagnóstico de 14 casos novos de hanseníase, sendo 13 classificadas como multibacilares. 23 Pesquisa evidenciou que muitos médicos brasileiros não conseguem determinar, prontamente, um diagnóstico conclusivo de hanseníase 22 , sendo que na região sudeste, 57,5% dos casos de hanseníase foram detectados por encaminhamento no período de 2015 a 2019 4 . O itinerário terapêutico das pessoas com hanseníase é marcado por um longo caminho e desafios em busca do diagnóstico 19,[24][25] , tanto na rede pública de saúde quanto na privada 25 .…”
Section: Resultsunclassified
“…A hanseníase é uma doença tropical negligenciada 1 que ainda persiste como problema de saúde pública em 23 , sendo que tanto no Plano Nacional 9 e no Estadual 10 da hanseníase existem recomendações para a vigilância da doença independentemente do nível de endemicidade. Mesmo havendo um compromisso político direcionando a construção de uma rede de atenção horizontalizada, hierarquizada, integral e integrada para atenção à saúde de pessoas com hanseníase e seus familiares 9-10 , que têm os serviços de APS como porta preferencial de entrada, pesquisas apontam que existem dificuldades na integração das ações de controle da hanseníase (ACH) nesse ponto de atenção [7][8]11 .…”
Section: Introductionunclassified
“…Summarizing and aggregating the results from our three previous published studies searching for HD involving prison male/female populations and from the community ( n = 2,133 evaluated individuals) in São Paulo state, the authors found 112 new cases of HD, with new case detection rate (NCDR) 6.5%; macular mild lesion in 93.7%; nerve impairment on palpation in 91.9 and 67% defined as having grade 2 disability (67%). On the other hand, APGL-I titer was positive in only 31.3% of the general population, 30.3% of the non-HD group and 54.4% of HD patients, although it was officially considered high for the non-endemic state, highlighting the hidden presence and the diagnostic challenge of HD and the low sensitivity as diagnostic test for new cases and screening contacts ( 8 , 30 , 31 ).…”
Section: Discussionmentioning
confidence: 96%